(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Acai berry /Euterpe oleracea mart. has a high antioxidant, anti inflammatory, antiproliferative,cardioprotective activities. The use of silver nanoparticles have great antibacterial and antimicrobial properties,nowadays it has been used in medical devices,wound dressing which releases silver in lower amounts to provide a microbe free environment. Cytotoxicity tests are very important in nanoparticles as they help in the determination of the proposed biomedical use to cause any cell death due to leaching of toxic substances or from direct contact of the nanoparticle.The aim of the study is to find the cytotoxic effect of silver nanoparticles using Acai berry fruit extract.All the materials used are under laboratory conditions.The brain shrimp lethality assay results show a low toxicity profile under the concentration of 80µL where there are 80%of viable napoli.